Chelating Phosphorus–An O, C, O‐Coordinating Pincer‐Type Ligand Coordinating PIII and PV Centres. Issue 58 (26th August 2022) - Gock, Michael; Lutter, Michael; Pintus, Anna; Schollmeier, Dieter; Arca, Massimiliano; Lippolis, Vito; Jurkschat, Klaus
Abstract: The sequence of reactions of the phosphorus‐containing aryllithium compound 5‐ t ‐Bu‐1, 3‐[(P(O)(O‐ i ‐Pr)2 ]2 C6 H2 Li (ArLi) with Ph2 PCl, KMnO4, elemental sulfur and elemental selenium, respectively, gave the aryldiphenylphosphane chalcogenides 5‐ t ‐Bu‐1, 3‐[(P(O)(O‐ i ‐Pr)2 ]2 C6 H2 P(E)Ph2 (1, E=O; 2, E=S; 3, E=Se). Compound 1 partially hydrolysed giving [5‐ t ‐Bu‐1‐(P(O)(O‐ i ‐Pr)2 ‐3‐(P(O)(OH)2 C6 H2 ]P(O)Ph2 (4 ). The reaction of ArLi with PhPCl2 provided the benzoxaphosphaphosphole [1(P), 3(P)‐P(O)(O‐ i ‐Pr)OPPh‐6‐ t ‐Bu‐4‐P(O)(O‐ i ‐Pr)2 ]C6 H2 P (5i ) as a mixture of the two diastereomers. The oxidation of 5i with elemental sulfur gave the benzoxaphosphaphosphole sulfide [1(P), 3(P)‐P(O)(O‐ i ‐Pr)OP(S)Ph‐6‐ t ‐Bu‐4‐P(O)(O‐ i ‐Pr)2 ]C6 H2 (5 ) as pair of enantiomers P1( R ), P3( S )/P1( S ), P3( R ) of the diastereomer ( RS/SR )‐5 (5b ). The aryldiphenylphosphane 5‐ t ‐Bu‐1, 3‐[(P(O)(O‐ i ‐Pr)2 ]2 C6 H2 PPh2 (6 ) was obtained from the reaction of the corresponding aryldiphenylphosphane sulfide 2 with either sodium hydride, NaH, or disodium iron tetracarbonyl, Na2 Fe(CO)4 . The oxidation of the aryldiphenylphosphane 6 with elemental iodine and subsequent hydrolysis yielded the aryldiphenyldioxaphosphorane 9‐ t ‐Bu‐2, 6‐(O H )‐4, 4‐Ph2 ‐3, 5‐O2 ‐2, 6‐P2 ‐4λ 5 ‐P‐[5.3.1.0]‐undeca‐1(10), 7(11), 8‐triene (7 ). Both of its diastereomers, ( RR / SS )‐7 (7a ) and ( RS / SR )‐7 (7b ), were separated as their chloroform and i ‐propanol solvates, 7a ⋅2CHCl3 and 7b ⋅ i ‐PrOH, respectively. DFT calculations accompanied the experimental work. Abstract : P=O→Element coordination keeps going and double cyclization involving the O, C, O‐coordinating pincer‐type ligand [5‐ t ‐Bu‐1, 3‐(P(O)(O‐ i ‐Pr)2 2 C6 H2 ] − was achieved for the first time in case of the aryldiphenyldioxaphosphorane 9‐ t ‐Bu‐2, 6‐(O H )‐4, 4‐Ph2 ‐3, 5‐O2 ‐2, 6‐P2 ‐4λ 5 ‐P‐[5.3.1.0]‐undeca‐1(10), 7(11), 8‐triene, existing as two diastereomers.